Peluang, Tantangan, dan Stategi Zakat dalam Pemberdayaan Ekonomi Umat - Siti Zumrotun (AHKAM : Jurnal Ilmu Syariah, 2016)
Basically, zakat in Islamic teaching is the one of effective and strategic ways to be developed in increasing prosperous of people. So, it can be very potential. The potency of zakat will be great and useful if the institution of zakat administrator can manage effectively and overcome all classic problems always faced by administrators. Managerial skill, accountability, integrity, and truth are the main capitals to manage zakat. Meanwhile, empowering, supervising, and teaching on the people who received zakat (mustahiq) are some important things that should be thought. Therefore, the institution of zakat management should get the way to change people perspective from receiver to giver (mustahiq to muzakki). The strategies are to accustom for paying zakat, to be creative and smart in collecting zakat, distribute zakat effectively, create high quality of human resources, and to be focus on the programs of developing zakat.DOI: 10.15408/ajis.v16i1.2899